2015
DOI: 10.1111/aor.12441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance and Safety of a Newly Developed Intravenous Fluid Warmer

Abstract: To evaluate the performance and safety of a newly developed blood warmer (ThermoSens), we tested its heating capability under various conditions using isotonic saline and hemolysis analysis with swine blood. The following two in vitro tests were performed: (i) To investigate the performance of the device, the inflow and outflow temperatures were measured at various flow rates (30, 50, and 100 mL/min) using cold (5°C) and room temperature (20°C) isotonic saline (0.9%). Several parameters were measured including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…The effectiveness of ThermoSens® and Ranger™ have been studied at different flow rates [571316]. However, there were no studies investigating whether ThermoSens® and Ranger™ can effectively deliver warm fluid at low and moderate flow rates (below 1000 ml/h) in clinical and laboratory conditions, except for Jung's report using Ranger™ [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of ThermoSens® and Ranger™ have been studied at different flow rates [571316]. However, there were no studies investigating whether ThermoSens® and Ranger™ can effectively deliver warm fluid at low and moderate flow rates (below 1000 ml/h) in clinical and laboratory conditions, except for Jung's report using Ranger™ [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no studies investigating whether ThermoSens® and Ranger™ can effectively deliver warm fluid at low and moderate flow rates (below 1000 ml/h) in clinical and laboratory conditions, except for Jung's report using Ranger™ [7]. ThermoSens® warms the fluid using a heating tube containing a heating plate, in direct contact with the fluid [13]. FloTem and JOYOTHER BM-1 (Joyother, Seoul, Korea) also employ the dry heat technology for warming the fluid with a tube heated by electric heater elements, similar to technology of ThermoSens® [1117].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaccaria Ricci et al of the Bambino Gesù Children's Hospital, IRCCS, Rome, Italy used multisite near infrared spectroscopy (NIRS) monitoring during pediatric cardiopulmonary bypass (CPB) to evaluate absolute values in a cohort of 25 infants undergoing pediatric cardiac surgery. Median Aristotle score was 8 , and vasoactive inotropic score at CPB weaning was 16 . Two‐way ANOVA showed that time and site significantly affected variations of NIRS values.…”
Section: Cardiopulmonary Supportmentioning
confidence: 99%
“…Hee Jung Kim et al of Korea University, Seoul, Korea evaluated the performance and safety of a new blood warmer. The highest outlet temperatures obtained using flow rates of 30, 50, and 100 mL/min were 39.10 ± 0.59, 39.25 ± 0.69, and 37.63 ± 1.03°C, respectively, with cold saline, and 39.40 ± 0.40, 39.66 ± 0.36, and 39.49 ± 0.49°C, respectively, with room temperature saline.…”
Section: Bioengineeringmentioning
confidence: 99%